Nurse educators' perceptions of the way nursing students protect patient privacy - Otília Zangão; Mendes Felismina
The aim of this study was to assess the teaching-learning process related to patient privacy during the care process and the way nursing students' protect patient privacy. Descriptive/correlational study using a qualitative approach and nonprobability sampling of 19 nurse educators from two schools of nursing. Data was collected using semi-structured interviews. Data analysis was undertaken using the SPSS version 20 and Alceste 2010 programs. The study complied with ethical standards. Two classes were assigned (protection of patient privacy and care process) with four subcategories (protection, empathy, relational competencies and technoscientific competencies).The findings show the need to adopt a reflective approach to the teaching-learning process by using experiential learning activities and real-life activities. We believe that intimacy and the protection of privacy should be core themes of nurse education and training.